2014
DOI: 10.4184/asj.2014.8.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Screw Configuration for Thoracolumbar Burst Fracture Treatment: Short versus Long Posterior Fixation Constructs with and without Anterior Column Augmentation

Abstract: Study DesignAn in-vitro study.PurposeThe current study is aimed at investigating the differences in stability between short posterior fixation (SPF), hybrid posterior fixation (HPF), and long posterior fixation (LPF) with and without anterior column augmentation using calcium phosphate bone cement (CaP) for treating burst fractures (BFs).Overview of LiteratureThe ideal treatment for thoracolumbar BF is controversial regarding the use of short or LPF constructs.MethodsSeven human thoracolumbar spines (T9-L4) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Peters et al [ 40 ], in their biomechanical study comparing short segment versus long segment fixation, found that long posterior fixation was the stiffest with and without anterior column augmentation in all loading conditions. The use of screws two above and two below has shown to not only enhance the stability but also allow effective reduction of kyphotic deformity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peters et al [ 40 ], in their biomechanical study comparing short segment versus long segment fixation, found that long posterior fixation was the stiffest with and without anterior column augmentation in all loading conditions. The use of screws two above and two below has shown to not only enhance the stability but also allow effective reduction of kyphotic deformity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 21,22 suggested that short segment pedicle screw fixation without bone fusion following postural reduction can be an effective and safe operative technique in the management of selected young patients with unstable burst fracture. Peters et al, 23 in their biomechanics study comparing short segment versus long segment fixation, found that long posterior fixation was the stiffest .The use of screws two above and two below has shown to not only enhance the stability but also allow effective reduction of kyphotic deformity. However, short posterior fixation alone has also shown to provide good clinical and radiological outcomes for certain fractures, particularly in the more lordotic middle and lower lumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has several limitations. First, long-segment fixation is required to provide adequate stability [14]. There is also a risk of lower fusion rates owing to the inability to insert a larger cage, unlike the anterior and lateral approaches [6].…”
Section: Discussionmentioning
confidence: 99%